2019
DOI: 10.1021/jacs.9b08627
|View full text |Cite
|
Sign up to set email alerts
|

Peroxide-Promoted Disassembly Reassembly of Zr-Polyoxocations

Abstract: Zr/Hf aqueous-acid clusters are relevant to inorganic nanolithography, metal−organic frameworks (MOFs), catalysis, and nuclear fuel reprocessing, but only two topologies have been identified. The (Zr 4 ) polyoxocation is the ubiquitous square aqueous Zr/Hfoxysalt of all halides (except fluoride), and prior-debated for perchlorate. Simply adding peroxide to a Zr oxyperchlorate solution leads to a striking modification of Zr 4 , yielding two structures identified by single-crystal X-ray diffraction. Zr 25 , isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 59 publications
1
51
0
Order By: Relevance
“…Different bonding behavior of Zn 2+ and Mn 2+ to U 70 in the solid-state are preserved in solution, further underlining the importance of these counterions on assembly processes. Transition metal toroid or wheel clusters have been previously discovered that include a Zr 25 ring polycation, an organically ligated neutral Mn IV 70 ring, and an anionic phosphate/acetate ligated Pd 84 ring . However, this is the first example of an An IV -oxo cluster that does not build symmetrically on a central An 6 core, similar to AnO 2 . ,,, U 70 and U 84 are the largest tetravalent actinide (or Zr/Hf IV ) molecular clusters observed to date, strategically isolated with nonconventional, high-valence countercations …”
Section: Introductionmentioning
confidence: 99%
“…Different bonding behavior of Zn 2+ and Mn 2+ to U 70 in the solid-state are preserved in solution, further underlining the importance of these counterions on assembly processes. Transition metal toroid or wheel clusters have been previously discovered that include a Zr 25 ring polycation, an organically ligated neutral Mn IV 70 ring, and an anionic phosphate/acetate ligated Pd 84 ring . However, this is the first example of an An IV -oxo cluster that does not build symmetrically on a central An 6 core, similar to AnO 2 . ,,, U 70 and U 84 are the largest tetravalent actinide (or Zr/Hf IV ) molecular clusters observed to date, strategically isolated with nonconventional, high-valence countercations …”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that the reactive peroxide ligand can disassemble Zr 4 square tetramers and cubic hexamers that dominate the solution phase chemistry of zirconium(IV). 35 Considering this regulatory effect of peroxo-ligands, 10 equiv of H 2 O 2 were added to a solution of 2 equiv of Zr(acac) 4 in acetone followed by the addition of (TBA)[GeW 10 ] ( Scheme 1 ). Note that acetone/H 2 O 2 mixtures should be handled with care due to possible formation of acetone peroxides .…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the negatively charged POMs, positively charged metal-oxo clusters (metal-oxo polycations) are quite rare (9,10), but in recent years, special attention has been paid to the development of the synthesis of cationic metal-oxo clusters (11)(12)(13)(14)(15) (18,19), and isolation of these clusters. While applications ranging from water purification to catalysis have been searched for Al 13 and its analogs (20)(21)(22), the research on cationic metal-oxo clusters, in general, is in its infancy, and most studies focus on the synthetic and structural aspects, while their functions remain practically unexplored.…”
Section: Introductionmentioning
confidence: 99%